An energy-saving idea for airconditioning systems in phased construction projects. - Santos, Arturo Martin B.
In multiple building projects wherein the buildings are constructed one by one, the number of standy chillers for the whole complex will be more than necessary if each building's air conditioning system is exclusive to itself. However, if the refrigeration plants of these buildings are interconnected, the number of standby units will be reduced compared to the conventional method of designing refrigeration plants for airconditioning in phased construction projects. This paper discusses the design concept undertaken by the DCCD Engineering Corporation for the Ayala Center in Makati.